MOLDOVA IN THE ERA OF INTERNATIONALIZATION: CHALLENGES AND REFORM STRATEGIES (PANGEEA, 2025)
This article examines the process of internationalization of higher education in the Republic of Moldova, focusing on the challenges and reform strategies, adopted by educational institutions. In the context of integration into the European Higher Education Area, Moldova faces challenges related to adapting to international standards, modernizing the curriculum and creating international academic partnerships. The article explores the solutions and policies implemented to increase the competitiveness of Moldovan universities on the global stage, emphasizing the importance of international collaboration and innovation in education.
Keywords: reform; internationalization; higher education; Republic of Moldova; International